2011
DOI: 10.4161/cc.10.21.17946
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor p53 induces expression of the pregnancy-supporting human chorionic gonadotropin (hCG)CGB7gene

Abstract: Successful pregnancy requires a functionally normal blastocyst encountering a receptive maternal endometrium. Interestingly, the cell cycle regulator and tumor suppressor p53 has been reported to support reproduction in mice by regulating the expression of the leukemia inhibitory factor gene in the maternal endometrium. However, in humans the hormonal system orchestrating successful pregnancy is considerably different from rodents. Particularly, the primate-specific dimeric glycoprotein hormone human chorionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
0
13
0
1
Order By: Relevance
“…HCT116 parental, HCT116 p53−/− and HCT116 p21−/− , kindly provided by Bert Vogelstein, 54 and NIH3T3 cells (ACC59, DSMZ) were grown as described 55 . Stably transfected HCT116 cell lines were created by transfecting promoter-reporter constructs based on the pGL4.14-Hygro vector (Promega) and selected with hygromycin (PAA) at a concentration of 500 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…HCT116 parental, HCT116 p53−/− and HCT116 p21−/− , kindly provided by Bert Vogelstein, 54 and NIH3T3 cells (ACC59, DSMZ) were grown as described 55 . Stably transfected HCT116 cell lines were created by transfecting promoter-reporter constructs based on the pGL4.14-Hygro vector (Promega) and selected with hygromycin (PAA) at a concentration of 500 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Transfections of control siRNA (medium GC content, Invitrogen) and validated Stealth™ p53 siRNA (Invitrogen, VHS40367) at a final concentration of 100 nM were performed with DharmaFECT-1 transfection reagent (Dharmacon, Chicago, IL, USA) at a final dilution of 1∶1000 according to the manufacturer’s instructions [36]. Cells were harvested after 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…LIF-deficient female mice have a defect in reproduction due to the complete lack of uterine decidualization at the implantation stage that leads to the failure of blastocyst implantation. The levels of LIF protein increase at the time of expected implantation in fertile women.It has been suggested that ER (estrogen receptor) and p53 cooperate in the regulation of blastocyst implantation through the induction of LIF and CGB7 (Sohr and Engeland, 2011). Leukemia inhibitory factor (LIF) is a cytokine that has been the focus of many studies (Aghajanova et al, 2009;Allegra et al, 2009;Rashid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%